Patterning as a signature of human epidermal stem cell regulation - Klein, Allon M. (The Royal Society, 2011)
Understanding how stem cells are regulated in adult tissues is a major challenge in cell biology. In the basal layer of human epidermis, clusters of almost quiescent stem cells are interspersed with proliferating and differentiating cells. Previous studies have shown that the proliferating cells follow a pattern of balanced stochastic cell fate. This behaviour enables them to maintain homeostasis, while stem cells remain confined to their quiescent clusters. Intriguingly, these clusters reappear spontaneously in culture, suggesting that they may play a functional role in stem cell auto-regulation. We propose a model of pattern formation that explains how clustering could regulate stem cell activity in homeostatic tissue through contact inhibition and stem cell aggregation.